Comparison of the surgeries for the ossification of the posterior longitudinal ligament-related cervical spondylosis: A PRISMA-compliant network meta-analysis and literature review. Issue 9 (5th March 2021) - Li, Sihan; Peng, Jiajie; Xu, Ruoying; Zheng, Rong; Huang, Minghan; Xu, Yongzhen; He, Youcheng; Chai, Yujuan; Song, Hongmei; Asakawa, Tetsuya
Abstract: Objective: We designed and performed a network meta-analysis to compare the clinical outcomes among the 5 surgeries—anterior cervical corpectomy and fusion (ACCF), anterior controllable antedisplacement fusion (ACAF), laminoplasty (LP), laminectomy (LC), and posterior decompression with instrumented fusion (PDF)—for patients with cervical spondylosis related to the ossification of the posterior longitudinal ligament (OPLL). Methods: Databases, including PubMed, EMBASE, Cochrane Library, Google Scholar, and Web of Science (firstly available-2019) were selected for literature search. We performed a network meta-analysis with the included studies. A Newcastle-Ottawa scale was employed to assess the study quality of the included studies. Results: Total 23 studies with 1516 patients were included in our analysis. We found that ACCF achieved the most improvement in the Japanese Orthopaedic Association Scores and excellent and good recovery rate, ACAF achieved the best improvement of the improvement rate and lordosis. LP got the best operative time and blood loss. Conclusions: Our results suggested that both anterior (ACCF and ACAF) and posterior (LP, LC, and PDF) procedures have their strengths and weaknesses. Clinicians need to select the most appropriate surgery with a comprehensive consideration of the clinical condition of each patient with OPLL-related cervical spondylosis.